2021
DOI: 10.3906/sag-2010-152
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of ambulance calls for patients over 65 years of age in İzmir, Turkey: a two- year retrospective analysis

Abstract: Background/aim: Analysis of interventions for special patient groups is important for the planning of health services, especially emergency medical services. In this study, we aimed to evaluate emergency medical service (EMS) interventions for the elderly and determine the decisive factors affecting transfer to the hospital of EMS team, over two years (2017)(2018) in İzmir. Materials and methods:Records of 112 emergency calls that were made between 2017 and 2018 followed up with interventions for patients aged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
(26 reference statements)
1
0
0
Order By: Relevance
“…Throughout the day, the utilization rate was observed to decrease at between 0 am and 6 am and to peak at noon. Several studies also reported similar findings [ 9 , 55 ]. In the prehospital EMS disease spectrum of the elderly, the main disease was found to be trauma and intoxication (23.70%).…”
Section: Discussionsupporting
confidence: 72%
“…Throughout the day, the utilization rate was observed to decrease at between 0 am and 6 am and to peak at noon. Several studies also reported similar findings [ 9 , 55 ]. In the prehospital EMS disease spectrum of the elderly, the main disease was found to be trauma and intoxication (23.70%).…”
Section: Discussionsupporting
confidence: 72%